Chemical Vapor Deposition of Cobalt and Nickel Ferrite Thin Films: Investigation of Structure and Pseudocapacitive Properties. Issue 20 (24th September 2021) - Zywitzki, Dennis; Schaper, Raoul; Ciftyürek, Engin; Wree, Jan‐Lucas; Taffa, Dereje H.; Baier, Daniel M.; Rogalla, Detlef; Li, Yujiao; Meischein, Michael; Ludwig, Alfred; Li, Zheshen; Schierbaum, Klaus; et al.
Abstract: Transition metal ferrites, such as CoFe2 O4 (CFO) and NiFe2 O4 (NFO), have gained increasing attention as potential materials for supercapacitors. Since chemical vapor deposition (CVD) offers advantages like interface quality to the underlying substrates and the possibility for coverage of 3D substrates, two CVD processes are reported for CFO and NFO. Growth rates amount to 150 to 200 nm h −1 and yield uniform, dense, and phase pure spinel ferrite films according to X‐ray diffraction (XRD), Raman spectroscopy, Rutherford backscattering spectrometry and nuclear reaction analysis (RBS/NRA) and scanning electron microscopy (SEM). Atom probe tomography (APT) and synchrotron X‐ray photoelectron spectroscopy (XPS) give insights into the vertical homogeneity and oxidation states in the CFO films. Cation disorder of CFO is analyzed for the first time from synchrotron‐based XPS. NFO is analyzed via lab‐based XPS. Depositions on conducting Ni and Ti substrates result in electrodes with pseudocapacitive behavior, as evidenced by cyclovoltammetry (CV) experiments. The interfacial capacitances of the electrodes are up to 185 µF cm −2 . Abstract : Two new metal organic chemical vapor deposition processes for the fabrication of dense, homogenous, and phase pure cobalt and nickel ferrite thin films are developed. To this end, molecularly designed precursors are chosen and the films thoroughly analyzed. Additionally, synchrotron‐based X‐ray photoelectron spectroscopy is used for cation disorder analysis for the first time. The resulting films are proven to be applicable as potential electrodes in supercapacitors.